2020
DOI: 10.3390/molecules25245978
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper Oxide on Epoxy Coatings with New Intumescent Polymer-Based Fire Retardant

Abstract: Epoxy resins (EP) have been used as a thermos-setting material in the field of coating, casting, bonding agent, and laminating. However, a major drawback associated with its use is the lack of good flaming properties, and it is responsible for heavy smoke along with hazardous gases considerably limiting its uses in various fields. In this study, N-ethanolamine triazine-piperizine, a melamine polymer (ETPMP), was established as a new charring-foaming agent and was successfully synthesized with ethanolamine, pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Riyazuddin et al synthesized polymeric flame retardants (ETPMP) by nucleophilic substitution reactions using ethanolamine, piperazine, and melamine, as raw materials. 96 ETPMP, APP and CuO were used in various ratios to prepare intumescent flame retardants (IFR and IFR/CuO). Flame retardant and smoke suppression tests were conducted and the results showed that the addition of a small amount of CuO significantly improved the LOI results and the UL-94 to V-0 level and the strength analysis results of epoxy, EP/IFR, and EP/IFR/CuO-5% sample charred layers is shown in Fig.…”
Section: Classification Of Metal-based Flame Retardantsmentioning
confidence: 99%
“…Riyazuddin et al synthesized polymeric flame retardants (ETPMP) by nucleophilic substitution reactions using ethanolamine, piperazine, and melamine, as raw materials. 96 ETPMP, APP and CuO were used in various ratios to prepare intumescent flame retardants (IFR and IFR/CuO). Flame retardant and smoke suppression tests were conducted and the results showed that the addition of a small amount of CuO significantly improved the LOI results and the UL-94 to V-0 level and the strength analysis results of epoxy, EP/IFR, and EP/IFR/CuO-5% sample charred layers is shown in Fig.…”
Section: Classification Of Metal-based Flame Retardantsmentioning
confidence: 99%
“…Chen et al [18] used dimethyldioxysiloxane condensed with 3-glycosyloxypropyltrimethoxysiloxane (KH-560) to prepare a silicone-modified epoxy resin-based coating (SiR) and cured the resin with a nitrogen-and a phosphorus-containing flame retardant (PTDP), which was able to achieve a V-1 rating in UL-94 testing, and the LOI value could reach 31%. Riyazuddin et al [19] prepared a novel melamine polymer (ETPMP) using nucleophilic substitution reaction and prepared epoxy resin-based flame-retardant coatings together with APP and CuO. The flame-retardant properties of the coatings changed significantly as soon as trace amounts of CuO were doped, with a 13% increase in LOI value and a UL-94 test rating of V-0.…”
Section: Introductionmentioning
confidence: 99%
“…The first issue is intrinsically related to the chemical structure of the CFRPs, and while it can be addressed with the choice of a convenient polymeric matrix, it cannot be completely overcome. The fire-related question can be mitigated by adding flame-retardant and/or flame-resistant additives to the matrix [7][8][9] or applying surface localized treatments in order to avoid bulk modification [10], and the latter by increasing the interlaminar fracture toughness [11][12][13], that is, the energy required for crack propagation. While bulk matrix toughening is possible, similar to the flame retardancy approach, it is undesirable due to the laminate weight increase and worsening of the overall thermomechanical properties [14,15].…”
Section: Introductionmentioning
confidence: 99%